Modificação física de farinha de araruta para aplicação em massa alimentícia enriquecida com coprodutos agroindustriais - Fideles, Marília Cândido (2019)
Arrowroot is a plant that has abundant starch content and does not present gluten in its composition, arousing the interest of its use in the production of pasta. However, gluten substitution must be provided through the use of techniques, such as the arrowroot flour modification through physical processes. Starch is the highest percentage of arrowroot composition, so enrichment of the dough is an interesting alternative, and a fortification with agroindustrial coproducts sources of fiber and protein, such as passion fruit peel and bovine rumen, may be viable. The objective of this study is to produce flours from agroindustrial coproducts, to modify by different methods (ultrassonic and heat-moisture treatment) the starch of arrowroot obtained and determine the viability technological and nutritional aspects of the use of modified flours and agroindustrial coproducts, source of fiber and protein, in the production of different types of pasta. The hydration, paste and thermal properties of raw and modified flours were evaluated. The results of the ultrasound treatments vary with the temperature between 35.83 and 62% with time between 5 and 15 minutes. For heat-moisture treatment, the best results were those using the lowest temperature (105 ° C) and shorter times (15 and 30 minutes). Taking into account the use of modified flours in the production of pasta, ultrasonic treatments with parameters of intensity of 43.5% and time of 15 min and heat-moisture treatment with 105 ° C for 15 min were selected. With the technological techniques of the pasta produced, it was possible to analyze and choose the best parameters to obtain a pasta with less cooking time, loss of solids, intermediate increase of pasta, and small values of firmness, angle Hue and C* chromaticity. The proximal composition of the pasta was satisfactory, being able to be characterized as a food with high protein content and high fiber content. The pastas with the greatest desirability are a good sensory acceptance. The results obtained have the possibility to develop and improve the pasta formulated with raw and modified arrowroot flour and agroindustrial coproducts.